Food Marketing and its Impact on Adolescents' Food Choices - Sivathanu, Brijesh (Indian Journal of Marketing, 2017)
Background : Now-a-days, adolescents and children are considered as a substantial target market by the food industry. This makes marketers to target children and adolescents by designing customized food advertising and marketing campaigns. Purpose : This empirical study scrutinized the impact of food marketing techniques on the food choices of adolescents. Methodology : A primary survey was conducted among 560 adolescents in the age group of 10 – 18 years and their parents using a structured questionnaire to understand the impact of various food marketing techniques on the food choices of the adolescents. To understand the impact of marketing techniques on the food choices of the adolescents, I used the multiple linear regression technique. Findings : The findings of this study clearly showed that repetition of the message, brand image, celebrity endorsements, premiums, product placements, viral marketing, integrated marketing strategies, attention getting products had a significant impact on the adolescents' food choices. The findings from the perception study of the parents showed that food marketing targeted at adolescents affected their food choices and influenced their health due to unhealthy food choices, making them a vulnerable consumer. Research Limitations : This research was conducted in the city of Pune in the state of Maharashtra. This study was specifically limited to the food marketing techniques targeted at adolescents. To increase the validity and reliability of this study, it can be tested in other cities of India. Practical / Managerial Implications : This study made both academic and practical benefactions. Academically, it added value to the current literature on food marketing techniques targeted at adolescents. It also helped marketers to understand the impact of food marketing on adolescents' food choices. Originality/Value : This study tried to connect food marketing and adolescent food choice behavior.